Path Analysis on the Determinants of Visual Inspection Acetic Acid Utilization on Early Detection of Cervical Cancer: Application of Health Belief Model Theory - Elfania Arumma Sunarta; Endang Sutisna Sulaeman; Uki Retno Budihastuti (Journal of Health Promotion and Behavior, 2019)
Background: Cervical cancer was a serious health problem for women and VIA screening provided many benefits to women, which was to detect early cervical cancer. This study aimed to determine the determinants that influence the use of VIA with the theory of Health Belief Model on women of reproductive age.Subjects and Method: This was an analytic observational study with a case-control approach, conducted in the working area of Wongsorejo Public Health Center, Banyuwangi, East Java from March to April 2019. The sampling technique used was Fixed Disease Sampling, with a ratio of 1:3. Samples from 150 women reproductive age who had not used VIA screening and 50 women who had conducted VIA screening. Independent variables were perceived susceptibility, perceived severity, perceived benefits, cues to action, self-efficacy, knowledge, attitudes, access to services and husband's support. The dependent variable was the use of VIA. Data were collected by questionnaire and analyzed by path analysis.Results: The use of VIA screening was directly affected and has a positive effect on perceived vulnerability (b= 1.45; CI 95%= 0.50 to 2.40; p= 0.003), perceived severity (b= 0.86; CI 95%= -0.16 to 1.88; p= 0.099), perceived benefit (b= 1.61; CI 95%= 0.52 to 2.68; p= 0.003), cues to action (b= 1.21; CI 95%= 0.05 to 2.37; p= 0.040), high efficacy (b= 1.26; CI 95%= 0.27 to 2.26; p= 0.012), attitude (b= 1.83; CI 95%= 0.81 up to 2.85) and husband support (b= 1.59; CI 95%= 0.63 to 2.55). The use of VIA screening was indirectly influenced by access to health services and knowledge.Conclusion: The use of VIA screening was directly influenced by perceived vulnerability, perceived severity, perceived benefits, perceived barriers, cues to act, self-efficacy, attitude and husband support. And it was indirectly influenced by access to services and knowledge.Keywords: VIA, Cervical Cancer, Health Belief Model, Path AnalysisCorrespondence: Elfania Arumma Sunarta. Masters Program in Public Health, Universitas Sebelas Maret, Jl. Ir. Sutami No. 36 A, Surakarta, Indonesia. Email: elfaniaas@gmail.com. Mobile: +6282272434301Journal of Health Promotion and Behavior (2019), 4(1): 32-42https://doi.org/10.26911/thejhpb.2019.04.01.04